2014
DOI: 10.1179/1351000214y.0000000090
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasmaortho-tyrosine/para-tyrosine ratio with responsiveness of erythropoiesis-stimulating agent in dialyzed patients

Abstract: Objectives Patients with end-stage renal failure (ESRF) treated with erythropoiesis-stimulating agents (ESAs) are often ESA-hyporesponsive associated with free radical production. Hydroxyl free radical converts phenylalanine into ortho-tyrosine, while physiological isomer para-tyrosine is formed enzymatically, mainly in the kidney. Production of 'para-tyrosine' is decreased in ESRF and it can be replaced by ortho-tyrosine in proteins. Our aim was to study the role of tyrosines in ESA-responsiveness. Methods Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The current data are in line with data obtained from our previous studies that we recalculated (The data presented in Figure S2 are based partly on literature data) [4,7,8,10]. These results further support the idea that diminished conversion of Phe to Tyr by PAH may be due to increased production of reactive oxygen species, which can cause a decrease in the cofactor BH4 that takes part in the enzymatic reaction [4,[7][8][9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current data are in line with data obtained from our previous studies that we recalculated (The data presented in Figure S2 are based partly on literature data) [4,7,8,10]. These results further support the idea that diminished conversion of Phe to Tyr by PAH may be due to increased production of reactive oxygen species, which can cause a decrease in the cofactor BH4 that takes part in the enzymatic reaction [4,[7][8][9].…”
Section: Discussionsupporting
confidence: 91%
“…The current study found that serum p-Tyr and the p-Tyr/Phe ratio were both lower in ACS patients compared to controls. Similar results have been described in patients with diseases associated with inflammation and immune activation, such as sepsis, diabetes, renal failure, and in burn patients [7][8][9][10].…”
Section: Discussionsupporting
confidence: 85%
“…There was also direct relationship of plasma o-Tyr/p-Tyr ratio and indices of EPO-resistance, as verified using correlation (with R values of approx. 0.4 and p values < 0.005) and regression analyzes [ 77 ].…”
Section: Chronic Diseases Associated With Oxidative Stressmentioning
confidence: 99%
“…Of note, 2-hydroxyphenylalanine can be generated by oxidative stress through the destruction by the hydroxyl radical of the benzyl ring of l-phenylalanine. 31 2-Hydroxyphenylalanine is therefore considered to be a biochemical marker of oxidative stress. 31,32 Taken together, the results indicating the presence of l-phenylalanine metabolic alterations in ACL injury models may show that l-phenylalanine could serve as a sensitive biomarker for cartilage degeneration by revealing matrix breakdown and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%